Effects of Fe-loaded biochar on the bioavailability of Arsenic and cadmium to lettuce growing in a mining contaminated soil. Issue 14 (20th June 2021) - Wu, Pingping; Li, Lujiu; Wang, Jing
ABSTRACT: Arsenic (As) and cadmium (Cd) are two prominent metal contaminants in mining soil, threatening food and environmental safety. The effects of Fe-loaded biochar on the accumulation and translocation of As and Cd in a soil-lettuce system were investigated to evaluate the efficiency of Fe-loaded biochar in reducing As and Cd bioavailability. Application of Fe-loaded biochar at a rate of 0.5–1.5% decreased the concentrations of porewater As and Cd by 4.2–53.0% and −0.6–21.7%, respectively. The results of sequential extraction showed that Fe-loaded biochar can promote the transfer of As and Cd in soils from the available fraction to a relatively stable fraction, thus reducing the mobility and availability of As and Cd. The concentrations of As and Cd in lettuce shoots in the Fe-loaded biochar treatment were significantly decreased by 11.4–26.0% and 4.4–12.9% compared with those in the untreated soil, respectively. Fe-loaded biochar applied at a rate of 0.5–1.0% had no obvious effect on plant biomass, and the lowest weight of lettuce shoots and roots was observed in the treatment with Fe-loaded biochar applied at a rate of 1.5%, in which they were reduced by 12.9% and 18.0%, respectively. Overall, Fe-loaded biochar as a soil amendment was effective in simultaneously reducing As and Cd bioavailability in As and Cd co-contaminated soils, and an application rate lower than 1.5% is recommended to avoid significant decreases in plant growth.